KEMAMPUAN SPASIAL PERCEPTION DALAM MENYELESAIKAN MASALAH GEOMETRI BERDASARKAN TEORI VAN HIELE DITINJAU DARI KEMAMPUAN MATEMATIKA - Amalia Mareta Pungkasari; FX. Didik Purwosetiyono; Agnita Siska Pramasdyahsari (Program Studi Pendidikan Matematika, 2020)
Difficulties in learning geometry relate to spatial abilities. Students with good spatial skills will be able to solve geometric problems. In helping students overcome difficulties in learning geometry, they used the Van Hiele's learning theory. This qualitative descriptive study aimed to describe the spatial perception ability in solving geometric problems based on Van Hiele's theory in terms of mathematical ability. The subjects in this study were three junior high school students with high, medium, and low math abilities. Subjects were given a spatial ability test and an interview twice. The triangulation time and subject was carried out to test the credibility of data. Based on the results of data analysis, students with high, medium, and low math abilities were able to observe objects from different perspectives. Subjects with medium math abilities were able to observe the object from different perspectives. However, subjects with high and low math abilities have some difficulties in observing objects from different perspectives.